Embedded System Prototype Driving Innovative Math Education - Claudino, Thais; Silva, Sarah Jane Souza da; Barbosa, Isnaldo Isaac (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware), 2025)
This article presents the proposal for the continuation of an interdisciplinary extension project that integrates mathematics education, technology, and social inclusion. The initiative originates from a board game aimed at teaching basic mathematical operations, already applied with elementary school students, and proposes its evolution into an interactive digital version. Through collaboration with the Embedded Systems program, a prototype is being developed that uses an interactive screen controlled by a microcontroller, capable of presenting mathematical challenges dynamically, with real-time visual and sound feedback. The project is based on the use of low-cost hardware and free software, reinforcing the connection between technology, education, and inclusion to create replicable pedagogical solutions with high social impact. The project is part of the context of active learning methodologies, exploring the potential of playfulness combined with open technology to promote greater engagement, autonomy, and inclusion in the educational process. In addition, it seeks to expand accessibility for students with disabilities, strengthening pedagogical practices aligned with the principles of inclusive education and the use of low-cost technologies with potential for replication in different school contexts. the results that motivated this next step refer exclusively to the application of the physical board game. That initial phase, which showed a significant increase in student engagement, was fundamental for validating the playful pedagogical approach and served as the foundation to justify and guide the development of the digital prototype, which constitutes the current phase of the project.